Analisis Pengaruh Transaksi Pembayaran Non Tunai Terhadap Jumlah Uang Beredar Di Indonesia - Devi Kartika Sari (Journal of Economics Development Issues, 2020)
The advancement of science and technology is always growing rapidly, no exception on financial technology. The development of financial technology has led to innovation payment systems from a cash payment system to a non-cash payment system. The study aims to determine the effect of non-cash transactions (credit card, ATM/debit card, and E-money) on the amount of money supply in Indonesia. Research using data sourced from Bank Indonesia (BI) and the Central Statistics Agency. The data used in this research is the quarter time series data between the years 2015(I) to the year 2019 (II). The analytical techniques used in this study multiple regression analysis. The result of this study indicate that non-cash transactions using credit cards, ATM/debit cards, and E-money simultaneously have significant effect on the amount of money supply (M1) in Indonesia. Partially, ATM/debit card significant impact on the amount of money supply (M1), while credit cards and E-money have no significant effect.